2013
DOI: 10.1021/ic401503b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of fac-[M(CO)3(P)(OO)] and cis-trans-[M(CO)2(P)2(OO)] Complexes (M = Re, 99mTc) with Acetylacetone and Curcumin as OO Donor Bidentate Ligands

Abstract: The synthesis and characterization of neutral mixed ligand complexes fac-[M(CO)3(P)(OO)] and cis-trans-[M(CO)2(P)2(OO)] (M = Re, (99m)Tc), with deprotonated acetylacetone or curcumin as the OO donor bidentate ligands and a phosphine (triphenylphosphine or methyldiphenylphosphine) as the monodentate P ligand, is described. The complexes were synthesized through the corresponding fac-[M(CO)3(H2O)(OO)] (M = Re, (99m)Tc) intermediate aqua complex. In the presence of phosphine, replacement of the H2O molecule of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…[36][37][38] Recently, even technetium complexes containing curcumin have been reported. 39 Moreover, curcumin complexes have been prepared for several lanthanide elements 2,[40][41][42][43] as well as thorium and uranium, with the latter all being uranyl (OQUQO) species. Pioneering work in this area was published in 1997 by Beck and co-workers at the Ludwig-Maximilians-Universität in Munich.…”
Section: How To Prepare and Characterize Metal Curcumin Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] Recently, even technetium complexes containing curcumin have been reported. 39 Moreover, curcumin complexes have been prepared for several lanthanide elements 2,[40][41][42][43] as well as thorium and uranium, with the latter all being uranyl (OQUQO) species. Pioneering work in this area was published in 1997 by Beck and co-workers at the Ludwig-Maximilians-Universität in Munich.…”
Section: How To Prepare and Characterize Metal Curcumin Complexesmentioning
confidence: 99%
“…22,23 Some technetium and rhenium curcumin complexes have recently been reported. 39 It was found that curcumin reacts with the bromide precursors fac-[M(CO) 3 Br 3 ] 2À (M = Tc, Re) through the b-diketonate moiety to generate, under mild synthetic conditions, the aqua complexes fac-M(CO) 3 (H 2 O)(Curc). .…”
Section: How To Prepare and Characterize Metal Curcumin Complexesmentioning
confidence: 99%
“…18). 104,105 The large trans effect exerted by triphenylphosphine can lead to further substitution and formation of [Re(CO) 2 (PPh 3 ) 2 L 24 ]. The substitution chemistry is similar for 99m Tc.…”
Section: Technetium-99m Radiotracers Designed To Bind To Amyloid-bmentioning
confidence: 99%
“…When incubated at 60 1C for 20 min, the reaction progresses to form cistrans-[ 99m Tc(CO) 2 (PPh 3 ) 2 L 24 ]. Both fac-[Re(CO) 3 L 24 (PPh 3 )] and cistrans-[Re(CO) 2 (PPh 3 ) 2 L 24 ] bind to Ab plaques in post-mortem human brain tissue 105.…”
mentioning
confidence: 99%
“…As monodentate ligands, phosphines (P), isocyanides (CNR), and aromatic amines have been used. Examples of bidentate ligands are the (N,O) donors such as 2‐picolinic acid (Figure .6); (O,O) donors of the keto‐enol type, like acetylacetone (Figure .7) or 3‐hydroxypyridone; (S,S) donors such as dithiocarbamate (Figure .8); (N,N) donors, like bipyridine; and (P,P) bisphosphine ligands, like 1,2‐bis(hydroxymethylphosphine)ethane . In [ 99m Tc(CO) 3 (P,P)(H 2 O)] complexes, the third position occupied by water is less reactive to substitutions due to the presence of the two strong π‐acidic phosphines.…”
Section: Technetium‐99m Complexesmentioning
confidence: 99%